Fiction, famine, and the rise of economics in Victorian Britain and Ireland - Bigelow, Gordon (Cambridge University, 2013)
At the time of the Irish Famine, novels by Dickens and Gaskell, and commentaries on the famine, introduced a new theory of individual expression, which gradually replaced the older ideas of political economy, and became the foundation for modern concepts of capitalism based on the desires of the individual consumer.